A new species of Tetralidia Marques-Costa & Cavichioli (Hemiptera: Cicadellidae: Neocoelidiinae) from Amazon Region - Gonçalves, Clayton Correa; Marques-Costa, Ana Paula; Ale-Rocha, Rosaly (Zootaxa, 2011)
A new species of Tetralidia Marques-Costa & Cavichioli, 2008, Tetralidia curvipenis sp. nov., is described and illustrated. The new species can be distinguished from the other species of the genus by the following characteristics: (1) style with apical third moderately curved ventrally; (2) connective Y-shaped; (3) aedeagus S-shaped with apical fifth abruptly curved ventrally and with pair of dorsal preapical spine-like processes, forming “V” in ventral view (4) anal tube with pair of moderately long basiventral processes, with slightly curved and sclerotized apices, reaching posteroventral margin of pygofer. A revised generic diagnosis and an identification key to males of the species are also provided.